CONCENTRATION OF HEAVY METALS ON ROOTS, STEM AND LEAVES OF Enhalus acoroides, IN TUNDA ISLAND, BANTEN BAY - Neviaty P Zamani; Tri Prartono; Ali Arman; Dewi S. Ariesta; Iswandi Wahab (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2018)
Heavy metal pollution is one of serious problem for tropical mangrove ecosystem. Heavy metals can decrease the quality of a waters. The decreasing in water quality can caused by pollutants such as heavy metals with high concentrations greatly affects the aquatic environment, especially living organisms. The aimed of study is to determine the accumulation level of heavy metals such as Al, Cu, Pb, As, Ni, Cr, Ti, Mn, dan Fe, in root, leaves and stem of E. acoroides. The sampling was carried out in the northern and southern parts of Tunda Island, in March 2015. The method used for seagrass destruction is 6 mL 65% HNO3 and mL H2O2 30%, sediment destruction using Milestone Start D microwave labstation. and using ICP-OES (Inductive Coupled Plasma-Optical Emission Spectrometry) Thermo Scientific iCAP 700 Series. The result show that, the Al, was the dominant heavy metals observed both in sea water and sediment surrounding the observed sea grass areas. Similar result was also observed for seagrass. The dominant sediment grain size absorbing heavy metals is silt-clay because it has more organic matter to control the binding of heavy metals. Heavy metal bioaccumulation is predominant in seagrass leaves and stems due to heavy metal entry into seagrass, substance storage tissue, and seagrass characteristics that are completely submerged in water. Seagrass meadow ecosystem in Tunda Island has been contaminated by several heavy metals.